2007
DOI: 10.1159/000110893
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Noninvasive Ventilation in Patients with Cystic Fibrosis

Abstract: Background: The benefits of long-termnoninvasive positive pressure ventilation (NPPV) have not yet been evaluated in patients with cystic fibrosis (CF). Objectives: To evaluate the effect of 1 year of NPPV on lung function in patients with advanced CF. Methods: Data were obtained from the French CF Registry. Patients who started NPPV (ventilated group, n = 41) were compared to matched controls (control group, n = 41). Each ventilated patient was matched to a control 1 year before the start of NPPV (year –1) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 41 publications
(32 reference statements)
0
31
0
3
Order By: Relevance
“…Single-centre data from the UK published in 2002 suggested that the mean duration of long-term NIV usage was just 1 to 2 months [9]. The clearest data on outcomes including lung function following NIV comes from a retrospective review of 41 patients from the French CF registry [10]. This suggested that NIV slows the decline in FEV 1 over 12 months of follow-up, raising the possibility of a role for NIV as part of maintenance pulmonary therapy in advanced CF.…”
Section: Introductionmentioning
confidence: 99%
“…Single-centre data from the UK published in 2002 suggested that the mean duration of long-term NIV usage was just 1 to 2 months [9]. The clearest data on outcomes including lung function following NIV comes from a retrospective review of 41 patients from the French CF registry [10]. This suggested that NIV slows the decline in FEV 1 over 12 months of follow-up, raising the possibility of a role for NIV as part of maintenance pulmonary therapy in advanced CF.…”
Section: Introductionmentioning
confidence: 99%
“…Chez le patient neuromusculaire, la VNI n'a pas d'effet bénéfique démontré sur la force des muscles respiratoires, la fonction respiratoire et la tolérance à l'exercice [28]. En revanche, grâce à une analyse des données de l'Observatoire français de la mucoviscidose, on a observé que la VNI était associée à une stabilisation de la fonction respiratoire chez les patients présentant une atteinte respiratoire sévère [29]. La VNI est également associée à une moindre fatigue des muscles respiratoires au cours de la kinésithérapie respiratoire chez les patients atteints de mucoviscidose.…”
Section: Amélioration De La Survieunclassified
“…However, these situations are characterized by an increase in minute ventilation and are thus associated with a lesser risk of alveolar hypoventilation, as compared with sleep. [20,24] Slowing of the decline in lung function [22] Improvement of respiratory muscle performance [16,18,19] Improvement of survival Improvement in exercise tolerance [14,21] Improvement in quality of life Spontaneous ventilation is the result of a balance between neurological mechanisms controlling ventilation together with ventilatory muscle power on one side, and the respiratory load, determined by lung, thoracic and airway mechanics, on the other. In patients with cystic fibrosis, the load imposed on the respiratory muscles is too high, which explains the occurrence of alveolar hypoventilation.…”
Section: Physiological Rationale For Nppv In Cfmentioning
confidence: 99%
“…However, the number of patients, as well as the duration of NPPV, may have been too small to confirm this benefit. Another study used the data of the French national CF registry to compare the evolution of lung function in patients that were started on NPPV to a group of comparable severity that was not started on NPPV [22]. This comparison showed that the patients who were started on NPPV experienced a significantly greater decline in lung function during the year prior to the start of NPPV than a matched control group.…”
Section: Preservation Of Respiratory Muscle Performance and Lung Functionmentioning
confidence: 99%